Enhancing natural gas-to-liquids (GTL) processes through chemical looping for syngas production: Process synthesis and global optimization. (8th May 2018) - Tso, William W.; Niziolek, Alexander M.; Onel, Onur; Demirhan, C. Doga; Floudas, Christodoulos A.; Pistikopoulos, Efstratios N.
Highlights: Two chemical looping processes are modeled using parameter estimation and disjunctive programming. Chemical looping is incorporated into the GTL process synthesis as an alternative for producing syngas from natural gas. A comprehensive GTL process superstructure is globally optimized to investigate the benefits of chemical looping. Chemical looping can drastically improve break-even oil prices for GTL refineries. Abstract: A process synthesis and global optimization framework is presented to determine the most profitable routes of producing liquid fuels from natural gas through competing technologies. Chemical looping is introduced into the framework for the first time as a natural gas conversion alternative. The underlying phenomena in chemical looping are complex and models from methods such as computational fluid dynamics are unsuitable for global optimization. Therefore, appropriate approximate models are required. Parameter estimation and disjunctive programming are described here for modeling two chemical looping processes. The first is a nickel oxide based process developed at CSIC in Spain; the second is a iron oxide based process developed at Ohio State University. These mathematical models are then incorporated into a comprehensive process superstructure to evaluate the performance of chemical looping against technologies such as autothermal reforming and steam reforming for syngas production. The rest of the superstructure consists of process alternatives for liquid fuels production from syngas and simultaneous heat, power, and water integration. Among the various case studies considered, it is shown that chemical looping can reduce the break-even oil prices for natural gas-to-liquids processes by as much as 40%, while satisfying production demands and obeying environmental constraints. For a natural gas price of $5/TSCF, the break-even price is as low as $32.10/bbl. Sensitivity analysis shows that these prices for chemical looping remain competitive even as natural gas cost rises. The findings suggest that chemical looping is a very promising option to enhance natural gas-to-liquids processes and their capabilities.